2003
DOI: 10.1002/jso.10281
|View full text |Cite
|
Sign up to set email alerts
|

New considerations for an overall approach to treat hepatocellular carcinoma in cirrhotic patients

Abstract: For small tumors and compensated cirrhosis, resection or radiofrequency could represent acceptable first line treatments. In addition to permit safe and immediate tumor control, this strategy would allow a preferential redistribution of grafts to patients with decompensated cirrhosis in whom transplantation is the only possibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0
1

Year Published

2004
2004
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 95 publications
0
12
0
1
Order By: Relevance
“…Therefore, for small (Ͻ3-5 cm) unresectable HCC, as is found in OLT candidates selected according to Milan criteria, RFA is now universally emerging as the treatment of choice. 2,[16][17][18][19][20][21] Nevertheless, RFA has not been adequately investigated as an adjunct to transplantation for patients awaiting OLT. One series including 15 patients transplanted after RFA showed a 3-year posttransplantation survival rate of 85%, with two (13%) recurrences.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, for small (Ͻ3-5 cm) unresectable HCC, as is found in OLT candidates selected according to Milan criteria, RFA is now universally emerging as the treatment of choice. 2,[16][17][18][19][20][21] Nevertheless, RFA has not been adequately investigated as an adjunct to transplantation for patients awaiting OLT. One series including 15 patients transplanted after RFA showed a 3-year posttransplantation survival rate of 85%, with two (13%) recurrences.…”
Section: Discussionmentioning
confidence: 99%
“…At our institution, the strategy for management of HCC has evolved with a multimodality algorithmic approach similar to that adopted in other centers, [16][17][18][19][20][21] incorporating RFA as the primary treatment method. RFA is used as a first-line therapy for single tumors up to 5 cm and three or fewer tumors each up to 3 cm, except in the presence of contraindications including proximity to central bile ducts, bowel, gallbladder, inaccessibility by image guidance, or Child-Turcotte-Pugh class C cirrhosis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[16][17][18] More recently, RFA has become a popular method for treatment of HCC and has been applied as an alternative primary therapeutic modality to hepatectomy in some patients with HCC. 19 A Japanese nationwide comparative study, which was one of the most extensive surveys based on analysis of comparable patients treated by PEIT or surgery, indicated that surgery gave a better overall survival than PEIT for patients with a single clinical Stage I tumor less than 2 cm, solitary 2-to 5-cm tumors at any liver function status, or two or three tumor nodules. 20 However, there have been no substantive studies published that adequately compare the therapeutic results of RFA with those of surgical resection.…”
mentioning
confidence: 99%
“…The only proven potentially curative therapy for HCC remains surgical resection, either partial hepatectomy or orthotopic liver transplant (OLT) (Donckier et al, 2003;Lau, 2000;Ryder, 2003). Systemic and regional treatment modalities are considered to provide palliation or if a patient is unlikely to survive surgical resection because of inadequate liver function, has multiple nonresectable lesions, or requires tumor growth control while awaiting liver transplant.…”
Section: Treatment Optionsmentioning
confidence: 99%